ADDITIONAL PROFESSIONAL OPPORTUNITIES LANGUAGE EDUCATIONAL PROGRAM AT A TECHNICAL UNIVERSITY - Primova Dilbar Khushvaktovna (American Journals, 2022)
The article discusses the possibilities of an additional language professional educational program that provides students of technical universities with an additional (to higher) qualification "Translator in the field of professional communication". The authors give an example of a developed pedagogical system that allows for effective training of a specialist in demand in the labor market, based on the selection of targeted, meaningful and methodological components of training.
Keywords: additional language professional educational program, graduate model, selection of program content, pedagogical system of specialist training.